An Iron Deficiency Anemia Case That Came with Raw Rice Consumption - ÇAMLI, AHMET ADİL; ÇAMLI, AHMET ADİL; KARATOPRAK, CUMALİ; KARATOPRAK, CUMALİ; ÇETİN, GÜVEN; ÇETİN, GÜVEN; ZORLU, MEHMET; ZORLU, MEHMET; ALAY, MURAT (My University, 2015)
Pica is the chronic consumption of edible or nonedible materials that is thought to be caused by mental problems, pregnancy, or anemia. We wanted to report this case, which we have not seen in the literature before, of a pica patient who consumed raw rice due to iron deficiency anemia. A 26-year-old female patient was brought to the internal medicine polyclinic by her mother with complaints of consuming a bowl of raw rice (200 gr) every evening. The patient was treated with parenteral ferik hydroxide + sucrose complex (2700 mg) for 5 days. After 15 days, when she came to control her will to eat raw rice had been lost completely. As a result, the attention of doctors and family members for pica due to treatable causes, such as anemia, will prevent many probable complications.
Keywords: Pica; Case Report; raw rice; iron deficiency anemia